2000
DOI: 10.1021/jm000200l
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and X-ray Crystal Structure of a Potent Dual Inhibitor of Thymidylate Synthase and Dihydrofolate Reductase as an Antitumor Agent

Abstract: A novel N-¿2-amino-4-methyl[(pyrrolo[2, 3-d]pyrimidin-5-yl)ethyl]benzoyl¿-L-glutamic acid (3a) was designed and synthesized as a potent dual inhibitor of thymidylate synthase (TS) and dihydrofolate reductase (DHFR) and as an antitumor agent. Compound 3b, the N7-benzylated analogue of 3a, was also synthesized as an antitumor agent. The synthesis of 3a was accomplished via a 12-step sequence which involved the synthesis of 2-amino-4-methylpyrrolo[2,3-d]pyrimidine (10) in 5 steps from 2-acetylbutyrolactone. Prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 63 publications
1
87
0
Order By: Relevance
“…The DHFR inhibitory activity of 2-amino-4-oxopyrrolo [2,3-d]pyrimidines such as 1 can be explained by rotating the NH 2 -C2 bond by 180° such that the N7 functions as the 4-amino moiety. 47 Since analogue 4 is a pyrrolo[3,2-d]pyrimidine, we cannot explain the increased DHFR inhibitory activity on the basis of a NH 2 -C2 bond rotation of 180°. The increase in activity against human DHFR of 4 over 1 can be explained on the basis of our molecular modeling where the C7 of 4 interacts with Phe31 of human DHFR and the N7 of 1 would not have the same interaction.…”
Section: Biological Evaluation and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The DHFR inhibitory activity of 2-amino-4-oxopyrrolo [2,3-d]pyrimidines such as 1 can be explained by rotating the NH 2 -C2 bond by 180° such that the N7 functions as the 4-amino moiety. 47 Since analogue 4 is a pyrrolo[3,2-d]pyrimidine, we cannot explain the increased DHFR inhibitory activity on the basis of a NH 2 -C2 bond rotation of 180°. The increase in activity against human DHFR of 4 over 1 can be explained on the basis of our molecular modeling where the C7 of 4 interacts with Phe31 of human DHFR and the N7 of 1 would not have the same interaction.…”
Section: Biological Evaluation and Discussionmentioning
confidence: 94%
“…The silica gel plug obtained was loaded onto a silica gel column and eluted with 9:1 ethyl acetate/nhexane The fractions containing the product (TLC) were pooled and the solvent was evaporated to afford 1.33 g (67%) of 28 as a white solid: TLC R f = 0. 47 …”
Section: 2-dimethyl-n-(6-methyl-4-oxo-45-dihydro-3h-pyrrolo[32-d]mentioning
confidence: 99%
“…For the synthesis of 6-9 (Scheme 1), we found that the N7-benzyl group was necessary to increase the solubility of the intermediates and, more importantly, facilitated the Sonogashira coupling reaction with acetylenes. Thus, we started with the N-benzylated analog 11 40 (Scheme 1). Compound 11 was coupled using the Sonogashira reaction with appropriately substituted iodobenzenes in the presence of tetrakis(triphenylphosphine)palladium(0) (Pd-(PPh 3 ) 4 ), copper(I) iodide (CuI), and triethylamine in dichloroethane.…”
Section: Chemistrymentioning
confidence: 99%
“…2,13,14 Gangjee et al 10,11 suggested a dual DHFR-TS inhibitor model and proposed two binding modes for the 2-amino-4-oxo-pyrrolo[2, 3-d]pyrimidine system as well as the 2,4-diamino-furo[2, 3-d]pyrimidine (Fig. 2), Gangjee et al 15 demonstrated that compound 10, a 4-methyl analog of compound 3, binds in the alternate mode to DHFR.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 10 however showed excellent dual DHFR-TS inhibitory activities. 15 Some of these analogs were also significantly cytotoxic to the growth of tumor cells in culture (EC 50 = 1.0 × 10 −7 to 1.0 × 10 −8 M). This cytotoxicity was attributed to the efficient poly(γ-glutamylation) by the enzyme folypoly-γ-glutamate synthetase (FPGS).…”
Section: Introductionmentioning
confidence: 99%